Case study of the level of oral questioning used by teachers in formative assessment during the mathematics teaching process in primary school - Mahmud, Muhammad Sofwan; Md. Yunus, Aida Suraya; Mohd Ayub, Ahmad Fauzi; Sulaiman, Tajularipin (Centro de Investigaciones en Ciencias Sociales y Humanidades America Latina, 2019)
This study was conducted to see whether there are varied level of oral questions in formative assessment practices for primary school mathematics subject. Oral questioning is one of the main techniques used in formative assessment. Different levels of oral questioning that are implemented effectively in formative assessments can help in improving student’s understanding in mathematics subjects. This qualitative study was conducted on two mathematics teachers at a primary school in the district Kuala Pilah, Negeri Sembilan, Malaysia. The data was obtained through observation techniques, interviews and document analysis. The findings showed that the teachers did not vary the level of oral questioning in their teaching process but rather focused on the use of low-level oral questions which are at the level of remembering and understanding. In addition, this gives students less opportunity to improve their thinking during the mathematics teaching process. The implication of the study is; teachers need to reinforce questioning techniques by focusing on questions that can stimulate student’s high-level thinking.